COMPUTATIONAL INVESTIGATION ON THE STRUCTURE AND NMR CHEMICAL SHIFTS OF ENDO-CONE [CS2(p-METHYLCALIX[4]ARENE)] COMPLEX - Hanggara Sudrajat; Muhammad S. Saefullah; Danis Sriwijaya; Mirta A. Putri; Ria Armunanto (Universitas Gadjah Mada, 2009)
The structure and NMR chemical shifts of endo-cone [CS2(p-methylcalix[4]arene)] complex have been computationally investigated using BIO+ force fields, semi-empirical (PM3) and ab initio (RHF/6-311G++(d,p)) calculations. The first comparison of ab initio NMR chemical shift calculations for a calix[4]arene inclusion complex with solid-state 13C NMR chemical shifts based on the 1:1 complex of p-methylcalix[4]arenes with carbon disulfide in endo-cone complexation mode has been reported. The results showed that ab initio (RHF/6-311G++(d,p)) NMR calculations of the host-guest [CS2(p-methylcalix[4]arene)] complex are in good agreement with experimental solid-state NMR data.